Plasma proteomics in patients with von Willebrand disease and hemophilia A highlights von Willebrand factor as main determinant of response to desmopressin treatment - Jessica del Castillo Alferez; Eva R. Smit; Alexander B. Meijer; Karin Fijnvandraat; Marieke J.H.A. Kruip; Tirsa T. van Duijl; Maartje van den Biggelaar (Research and Practice in Thrombosis and Haemostasis)
Background: Desmopressin, 1-deamino-8-D-arginin vasopressin (DDAVP), is a treatment option for people with von Willebrand disease (VWD) and hemophilia A (HA) with a large interindividual variation in response. DDAVP elicits the release of von Willebrand Factor (VWF) from endothelial cells, thereby increasing the levels of circulating VWF and coagulation factor (F)VIII. However, we currently lack detailed insight on additional systemic effects of DDAVP administration on plasma protein levels. Objectives: This study aimed to investigate plasma proteomic profiles associated with DDAVP administration. Methods: Longitudinal plasma samples of 13 patients with VWD and 9 people with mild HA up to 24 hours after DDAVP infusion were analyzed using mass spectrometry–based proteomics. Results: Among 408 proteins quantified in plasma, only VWF and VWF propeptide (pp) increased significantly at 1 and 2 hours after DDAVP infusion in people with HA and VWD, respectively. VWF antigen levels were in agreement with mass spectrometry–based VWF intensity levels (ρ = 0.89). A slower clearance was observed for VWF compared with that for VWFpp, accompanied with higher interindividual variation. In 4 people with HA, C-reactive protein levels increased 24 hours after DDAVP infusion, which correlated with serum amyloid A1/A2 levels. Conclusion: This study showed the selective increase of VWF and VWFpp 1 to 2 hours after DDAVP infusion and highlighted the interindividual variance in VWF clearance. Additionally, a delayed acute-phase response in a subgroup of patients suggested the potential role of inflammatory mechanisms contributing to heterogeneity of response.